2016
DOI: 10.1002/cncr.30063
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent chemoradiotherapy versus radiotherapy alone for “biopsy‐only” glioblastoma multiforme

Abstract: BACKGROUND Combined temozolomide and radiotherapy (RT) is the standard postoperative therapy for glioblastoma multiforme (GBM). However, the clearest benefit of concurrent chemoradiotherapy (CRT) observed in clinical trials has been among patients who undergo surgical resection. Whether the improved survival with CRT extends to patients who undergo “biopsy only” is less certain. The authors compared overall survival (OS) in a national cohort of patients with GBM who underwent biopsy and received either RT alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Other prospective and retrospective studies, including a recent analysis of the NCDB database for patients aged ≥65 years diagnosed with GBM between 2005 and 2011, show that patients treated with chemoradiation may have better outcomes than patients treated with chemotherapy or RT alone . A smaller NCDB analysis of GBM patients between 2006 and 2011 who received biopsy only also showed that chemoradiation was superior to RT alone . In addition, likely reflecting the use of SCRT in the setting of clinical trials, we found that academic centers were more likely to administer SCRT compared to community programs.…”
Section: Discussionsupporting
confidence: 50%
“…Other prospective and retrospective studies, including a recent analysis of the NCDB database for patients aged ≥65 years diagnosed with GBM between 2005 and 2011, show that patients treated with chemoradiation may have better outcomes than patients treated with chemotherapy or RT alone . A smaller NCDB analysis of GBM patients between 2006 and 2011 who received biopsy only also showed that chemoradiation was superior to RT alone . In addition, likely reflecting the use of SCRT in the setting of clinical trials, we found that academic centers were more likely to administer SCRT compared to community programs.…”
Section: Discussionsupporting
confidence: 50%
“…In recent years, CCRT followed by adjuvant TMZ is the standard treatment for postoperative HGG patients. The regimen had more favorable survival rates than those who did not undergo this treatment and tolerable toxicity [17,18]. The application of molecular biology for precision medicine can accurately reflect the molecular biological characteristics and clinical treatment effects and prognosis of glioma [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…At this, the effect of concurrent CRT compared to EBRT alone was analyzed by Kole et al . [20]. Using the National Cancer Database, the authors identified patients with histologically confirmed, biopsy only GBM who were treated from 2006-2011.…”
Section: Discussionmentioning
confidence: 99%